THU0616-HPR EXPIRATORY FLOW ACCELERATOR (EFA) IN SYSTEMIC SCLEROSIS PATIENTS WITH MUCUS HYPERSECRETION, PRODUCTIVE COUGH AND DYSPNOEA: PRELIMINARY RESULTS FROM A HOME-BASED AIRWAY CLEARANCE TECHNIQUE DAILY PROGRAM. (2nd June 2020) - Faverzani, S.; Becciolini, A.; Crisafulli, E.; Nocera, F.; DI Donato, E.; Mozzani, F.; Riva, M.; Santilli, D.; Monica, L.; Barbieri, A.; Barone, L.; Marvisi, M.; et al.
Abstract : Background: Systemic sclerosis (SSc) is a chronic disease with frequent lung involvement. As mucociliary clearance is impaired, mucus retention and frequent pulmonary infections, increase morbidity and mortality (1). Airway clearance techniques (ACT) enhance removal of mucus from the airways. Expiratory flow accelerator (EFA) is a new technology that promotes deep and gentle drainage of the bronchial secretions, through the Venturi effect. No respiratory effort is required and no negative pressure is generated, avoiding risk of bronchial collapse (2). Objectives: The aim of this study was to describe the effectiveness of EFA in improving pulmonary symptoms in SSc patients. Methods: SSc patients with daily productive cough, frequent pulmonary exacerbations, exertional dyspnea and/or reduced physical activity were selected. All of them underwent a home-based ACT program with EFA. A Respiratory Physiotherapist (RT) trained each patient to use the device 3 times a day, 15 minutes each session. Every subject compiled the Saint George's Respiratory Questionnaire (SGRQ) and scleroderma Health Assessment Questionnaire (SHAQ) at baseline, 30, 90 and 180 days from the beginning. Statistical analysis has been carried out with General linear model for repeated measures. A value of p<0.05 was considered statistically significant. Results: 8 patients were enrolled (M:F=1:7), median age 54 (IC95% 46-69) years. Interstitial lung disease affected the majority of them (7/8). SGRQ total score and SHAQ domain for respiratory symptoms decreased over time (p= 0.003 and p= 0.005). In particular, there was an improvement in two SGRQ domains: activities (p= 0.013) and symptoms (p= 0.005) (fig.1 ). Conclusion: This is the first study to investigate the effect of EFA technology on airway clearance in SSc patients. The observations suggest the importance of a daily ACT program with EFA in improving respiratory symptoms. This technology appear to be extremely promising in SS patient management as it is well tolerated and it has the potential to slow down the pulmonary disease progression by limiting bronchial infections. References: [1]Tyndall AJ et al. Causes and risk factors for death in systemic sclerosis: a study from the EULAR Scleroderma Trials and Research (EUSTAR) database. Ann Rheum Dis 2010;69:1809–15. [2]Zampogna E, et al. Expiratory Flow Accelerator (EFA) technique on mucus hypersecretion of COPD patients with reduced cough efficiency after a severe exacerbation. Int Clin Med 2019;3:1-6. Disclosure of Interests: Silvia faverzani: None declared, Andrea Becciolini Speakers bureau: Sanofi-Genzyme, UCB and AbbVie, ernesto crisafulli: None declared, filippo nocera: None declared, eleonora di donato: None declared, Flavio Mozzani: None declared, michele riva: None declared, Daniele Santilli: None declared, lorenza monica: None declared, annalisa barbieri: None declared, lissette barone: None declared, maurizio marvisi: None declared, veronica alfieri: None declared, annalisa frizzelli: None declared, Alfredo Chetta: None declared, ALARICO ARIANI: None declared